Active vibration control for seismic excited building structures under actuator saturation, measurement stochastic noise and quantisation. (1st February 2018) - Xu, Lanlan; Yu, Yunyan; Cui, Yanliang
Highlights: By integrating the actuator saturation, stochastic measurement noise and quantisation, an observer-based feedback AVC law is proposed. Since the observe state is not influenced by seismic excitation and measurement noise, the proposed control law contributes to improve system robustness. By the proposed method, not only system mean square stability can be guaranteed almost surely but also an hybrid H2 /H∞ performance can be simultaneously achieved. The structural responses can be reduced in different level by regulating sensor and controller locations. More significantly, the convergence rate of close-looped system can be prescheduled. Abstract: This paper investigates the active vibration control for seismic excited building structures in presenting of actuator saturation, stochastic measurement noise and quantisation. The active vibration controllers are placed in some storeys, meanwhile, some active tuned mass dampers (ATMDs) are also installed at the top floor and oscillating under their control forces. All of the control forces are generated by actuators which are only capable of providing limited outputs. Since the system states are difficult or barely impossible to be accurately measured, an observer based control law is proposed to guarantee system stability, meanwhile, an H 2 / H ∞ index is employed for further improving the control performance. By the proposed control strategy, the mean square exponentially stability of close-looped system can be guaranteed almost surely while the desired H 2 / H ∞ performance can be achieved simultaneously. In addition, the convergence rate of system state can be pre-scheduled. By regulating the different locations of sensors and controllers, the vibration response can be mitigated in different level. Numerical examples are provided to demonstrate the effectiveness of the proposed method.